Best Practice Recommendations for Conducting and Reporting Controlled Trials in Clinical Hypnosis Research - Zoltan Kekecs PhD; Donald Moss PhD; Peter J. Whorwell MD, PhD; Katalin Varga PhD; Devin B. Terhune PhD; Philip D. Shenefelt MD; Olafur S. Palsson PsyD; Giuseppe De Benedittis MD, PhD; Gary Elkins PhD (SAGE Publishing, 2024)
There is an abundance of outcomes research for clinical hypnosis showing promising results. Nonetheless, hypnosis is still underutilized in clinical care. For a behavioral intervention to enter mainstream clinical care, efficacy needs to be demonstrated with exceptionally high quality of evidence, and its reporting needs to be complete and sufficiently clear to enable replication and clinical use. The present article provides best practice guidelines formulated by the Task Force for Establishing Efficacy Standards for Clinical Hypnosis for conducting and reporting clinical hypnosis research.The recommendations are presented in two tiers. Tier I recommendations include essential best practices, such as a call for the use of detailed research and intervention manuals, plans for and reporting of participant-education about hypnosis, the use of hypnotizability scales with good psychometric properties, and clear reporting of the hypnotizability measurement. Tier I also includes the sharing of intervention manuals, the reporting of the induction procedure, the labeling of the intervention for participants, and the definition of hypnosis used. Tier II includes preferred recommendations, calling for measurement of adherence to home practice, measurement of hypnotizability using scales with both subjective and behavioral measures of responsiveness, and the involvement of participants from the full hypnotizability spectrum. Tier II also includes the assessment of variables related to proposed mechanisms of action, the reporting of participants prior hypnosis experiences, and the relationship of expectancies and treatment outcomes.This list of recommendations will be useful for researchers, reviewers, and journal editors alike when conducting, reporting, or evaluating studies involving clinical hypnosis.